Social and Economic Vulnerability of Roma People Key Factors for the Success and Continuity of Schooling Levels - Mendes, Maria Manuela; Magano, Olga; Toma, Stefánia (Springer International Publishing : Imprint: Springer, 2021)
This open access volume provides an understanding of the different aspects of success, school continuity and social mobility among European Roma, including the motives justifying the high rates of school dropout and failure among this group. It offers a critical and reflexive perspective about social reality from a multidisciplinary and transversal point of view, sharing knowledge and practices in different countries about the articulations between Roma families, individuals, school and public policies. Over time, there has been an increase in the educational attainment of European citizens, but there are still persistent inequalities between Roma and non-Roma, including gender inequalities, which greatly affect Roma women. The volume explores the issue of Roma education and includes chapters from Western European, South and Central and Eastern European researchers using different theoretical and methodological perspectives. The intersection of this diversity and plurality of standpoints makes possible to obtain a comprehensive view on the education and schooling of European Roma.